Comparative analysis of HIV data completeness in Haiti’s iSanté Plus Electronic Medical Record system across children, adolescents and adults: a cross-sectional evaluation of 2016–2022 data - James P Hughes; Stephen Gloyd; Bradley Wagenaar; Nancy Puttkammer; Beryne Odeny; Jean Guy Honoré; Jean Gabriel Balan; Kemar Célestin; Marinho Elisma; Kesner Francois (BMJ Open)
Objective To evaluate and compare documentation completeness of HIV-related data by age group (children, adolescents and adults) in Haiti’s Electronic Medical Record (EMR) system.Design Cross-sectional evaluation.Setting EMR data for 36 965 enrolment visits, and 123 608 return visits from 58 facilities in Haiti (from 2016 to 2022).Participants Children, adolescents and adults accessing HIV care and treatment services in Haiti.Main exposure measure Health facility attendance for HIV-related healthcare.Main outcome measure Level of data completeness, as a measure of data quality. We developed Composite Completeness Scores (CCS scores) to measure data completeness. Lower scores meant lower completeness. Generalised linear models were used to investigate factors associated with completeness.Results At the enrolment visit, most patients were adults (81.6%) and female (56.7%). Most facilities were health centres (75.9%). The overall average enrolment visit CCS score was 54.0%. At enrolment, being a child (CCS score difference=−7.08, 95% CI: −11.31 to −2.86) and a more recent year of enrolment (−6.01, 95% CI: −11.69 to −0.33) were significantly associated with lower completeness scores than being an adult and having an earlier year of enrolment, respectively. The overall average return visit CCS score was 49.6%. At the return visit, children (−6.76, 95% CI: −10.07 to −3.45) had significantly lower average completeness scores than adults. For first viral load documentation, children had lower odds of completeness compared with adults (adjusted OR=0.21, 95% CI: 0.16 to 0.28). Sex, year of enrolment, facility ownership (public, private, mixed), total patient volume and duration of EMR use were not significantly associated with completeness of documentation at the enrolment and return visits.Conclusions We observed disparities in electronic data completeness by age group, which may be indicative of digital health disparities. Documentation was particularly poor among children and declined over time for enrolment visits. Further research is needed to understand and address these documentation gaps.